Analisis Strategi Keunggulan Bersaing (Competitive Advantage) pada Balai Diklat Keuangan Makassar - Azwar Iskandar (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This study aims to analyze strategic factors both from the internal and external environment of Makassar Financial Training and Education Center in order to develop a competitive advantage strategy. This study uses descriptive-qualitative research, with primary data consisting of data generated directly from respondents containing questions on the questionnaire sheet and secondary data obtained and available to the relevant agencies or units. Data analysis techniques used are IFAS (Summary of Internal Factory Analysis) and EFAS (Summary of External Factory Analysis) in the development of SWOT analysis. The results showed that: (1) Makassar Financial Education and Training Center in terms of development strategies have tried as optimal as possible to utilize the strengths to reduce weaknesses while the strength factor is greater than the weakness factor; (2) Makassar Financial Education and Training Center in competitive competition, placed in a relatively good position in the competition for the external environment where Makassar Financial Education and Training Center in terms of strategic development has tried its best to take advantage of existing opportunities to encourage external organization; (3) Makassar Financial Education and Training Center is currently in a strong and potential position. The strategy recommendations given are progressive in nature, where organizations in such prime and steady conditions are urgently needed to further enhance, enhance growth and obtain maximum progress; (4) The competitive advantage strategies of the Makassar Financial Education and Training Center are currently with the assistance and implementation of training programs using local wisdom in South Sulawesi in particular and Eastern Indonesia in general, for example in the tourism, culinary, and creative economy sectors and increasing The frequency of open open classes outside of regular training / training takes into account the special state financial needs of the Regional Government and there is a disruption of information technology.